Effects of dietary nucleotides on growth, survival and metabolic response in whiteleg shrimp, Litopenaeus vannamei against ammonia stress condition - Annita Seok Kian Yong; Wai, Yee Mok; Mohamad Tamrin Mohammad Lal; Rossita Shapawi; Yang‐Su Kim (Blackwell Publishing Inc., 2020)
This trial was conducted to evaluate the effects of nucleotides on growth of whiteleg shrimp, Litopenaeus vannamei , and the survival and metabolic responses to ammonia stress test. Experimental diets were as follows: low fish meal diet (LFMD), and four LFMD test diets, each supplemented with 0.1% guanosine monophosphate (GMP), 0.1% inosine monophosphate (IMP), 0.1% mixture of GMP and IMP and 0.1% mixture of GMP, IMP, uridine monophosphate (UMP) and cytidine monophosphate (CMP). The shrimp specimens (initial body weight: 0.99 ± 0.01 g) were randomly allocated into five groups and fed four times daily for 8‐weeks. After the trial, final body weight was recorded and haemolymph was withdrawn for haematological analysis. The shrimp was then challenged with 70 mg/L ammonia (LC50) for 10 days. Survival and haemolymph of the shrimp were taken after exposure to ammonia. The highest growth performance was observed in the shrimp fed diet supplemented with GMP (p < .05), while survival was not influenced by the test diets in the feeding trial. In the ammonia challenge test, the highest survival was observed in the shrimp fed GMP supplemented diet compared to others. The plasma protein, glucose and cholesterol levels increased in all the treatments while triglycerides level decreased post challenge. Cortisol level recovered at day 10th after the challenge. Shrimps fed with nucleotides diets showed higher protein and glucose level compared to control groups post challenge. In general, nucleotides supplemented in the diet enhanced growth, improved stress resistance while modulating the haemolymph metabolites in L. vannamei under ammonia stress.